ANALYSIS OF THE EFFECTIVENESS OF THE ELDERLY HEALTHY BEHAVIOR MODEL WITH THE THEORY OF PLANNED BEHAVIOR APPROACH IN PANTAI LABU DISTRICT, DELI SERDANG - Masdalifa Pasaribu (MEDALION JOURNAL: Medical Research, Nursing, Health and Midwife Participation, 2022)
The Theory of Planned Behavior (TPB) method can shed light on the factors that influence healthy intentions and behaviors in the aged. The purpose of this study is to evaluate the success of the aged healthy behavior model in Pantai Labu District, Deli Serdang, using the TPB approach, as well as to investigate the relationship between attitudes, subjective norms, perceived behavioral control, intents, and healthy behaviors. This study was designed as a descriptive survey using a quantitative technique. The sample consisted of 104 elderly people aged 60 years and over, who were part of a population of 1,085 people in Pantai Labu District. Data were collected using a questionnaire that measured attitudes towards healthy behavior, subjective norms, perceived behavioral control, intentions, and actual healthy behaviors. Data analysis was carried out using validity and reliability tests, multiple regression analysis, and Pearson correlation tests. The study showed that attitudes towards healthy behaviors had the greatest influence on the elderly's intention to live a healthy lifestyle (β = 0.45). Subjective norms and perceived behavioral control also had significant effects, with coefficients β = 0.30 and β = 0.25, respectively. The TPB model explained 68% of the variation in healthy behavioral intentions. The relationship between intention and actual healthy behavior showed a significant positive correlation (r = 0.72), indicating that strong intentions were related to the implementation of healthy behaviors. The TPB model was effective in explaining the factors that influenced healthy behaviors in the elderly in Pantai Labu District. Positive attitudes, social support, and perceived behavioral control contributed significantly to the intention of the elderly to adopt a healthy lifestyle. This study recommends the development of interventions that focus on improving attitudes, social support, and overcoming the barriers faced by the elderly in implementing healthy behaviors.